Comparative study on flame retardancy of multiple solid super acids-containing epoxy resin composites. (December 2020) - Chen, Xuexi; Shen, Jiahui; Wan, Mei; Gao, Ming; Yue, Lina
Abstract: Five different solid superacids (SO4 2− /TiO2 -MX OY ), including SO4 2- /TiO2 -CuO, SO4 2- /TiO2 -ZrO2, SO4 2- /TiO2 -Fe2 O3, SO4 2- /TiO2 -MnO, and SO4 2- /TiO2 -MoO3, were successfully synthesized and characterized. Then, the fire retarded performance, smoke suppression and thermal stability of the epoxy resin (EP)/melamine coated ammonium polyphosphate (MAPP)/SO4 2− /TiO2 -MX OY composites were investigated in details. The results showed that these SO4 2− /TiO2 -MX OY can effectively enhance the limiting oxygen index (LOI) values of the EP/MAPP composites. Compared with that of the EP/MAPP composites, the total heat release (THR) values of the EP/MAPP/SO4 2− /TiO2 -Fe2 O3, EP/MAPP/SO4 2− /TiO2 -ZrO2, EP/MAPP/SO4 2− /TiO2 -MnO and EP/MAPP/SO4 2− /TiO2 -MoO3 composites were remarkably reduced by 6%, 27 %, 32 % and 25 %, respectively, and the peak of heat release rate (PHRR) values of the EP/MAPP/SO4 2− /TiO2 -Fe2 O3, EP/MAPP/SO4 2− /TiO2 -ZrO2, EP/MAPP/SO4 2− /TiO2 -CuO, EP/MAPP/SO4 2− /TiO2 -MnO and EP/MAPP/SO4 2− /TiO2 -MoO3 composites were reduced by 0.3 %, 56.8 %, 23.6 %, 26.9 % and 36.9 %, respectively. Moreover, for the solid superacids-containing EP composites, the initial decomposition temperatures ( T i ) and the temperatures at the maximum mass loss rate ( T Max ) were advanced, and the char yields at 800 °C were much increased, which was indicated the considerable effect on the thermal degradation and char formation. Hence, the MAPP and SO4 2− /TiO2 -MX OY had good synergistic flame retardancy and smoke suppression, and the best for SO4 2− /TiO2 -MnO.